Do Primitively Eusocial Wasps Use Queen Pheromones to Regulate Reproduction? A Case Study of the Paper Wasp Polistes satan - Oi, Cintia A.; Oliveira, Ricardo C.; van Zweden, Jelle S.; Mateus, Sidnei; Millar, Jocelyn G.; Nascimento, Fabio S.; Wenseleers, Tom (Frontiers in Ecology and Evolution, 2019)
In several highly eusocial insect species with morphologically distinct castes, queen-characteristic cuticular hydrocarbons (CHCs) have been shown to act as queen signals that suppress the reproduction of nestmate workers. However, it is not known whether such queen pheromones might also play a role in regulating reproductive division of labour in primitively eusocial insects that lack morphologically defined castes. Here, we experimentally tested whether a blend of CHCs which occurred in higher concentrations in the dominant breeding female act as a queen pheromone, and inhibit reproduction by subordinate females in the primitively eusocial paper wasp Polistes satan. In contrast to earlier findings with highly eusocial species, our results show that although specific compounds were enhanced in dominant, reproductively active females, a blend of five of these compounds did not inhibit development of the ovaries of female nestmates. Instead, the dominant female had to be physically present to prevent subordinate females from reproducing. Our results are in line with earlier evidence suggesting that fertility-linked compounds in primitively eusocial wasps act only as cues and help to regulate reproduction when used in conjunction with aggressive dominance behaviour, meaning the physical presence of the dominant female. Alternatively, our results support the hypothesis that queen pheromones in highly eusocial insects were co-opted from fertility cues that were already present in primitively eusocial ancestors, even when initially, such compounds were merely produced as by-products of ovarian activation, without actually serving to signal reproductive status.